An evaluation of business models in e-mobile payment by using multiple criteria decision making - Pourali, Abdolghader; Hashempour, Elham (Journal of Advanced Computer Science & Technology, 2015)
Due to the significant growth in the usage of cell phone by customers and its availability, this tool can be considered such the best tool. For e-payment for implementing the mobile payment service, other objects and players should be considered such as banks, operators, service providers and the used technology as the effective interaction role. In addition, for effective optimization of parameters for implementing the mobile payment solution a proper model of business should be used. First of all, in this experiment, different business models in the field of mobile payment and the role of each stakeholder in these models and their positive and negative points are discussed. Moreover, by using method of Multiple Criteria Decision Making, four famous business models of the world are evaluated and the result of this evaluation highlights that the cooperation model is the most Appropriate Model in terms of mobile payment methods.